Characterizing and Analyzing Morphometric Parameters and Their Implica-tions on Watershed management in Sub-upper Wabe Shebele Drainage Basin, West Arsi Zone, Ethiopia: Research article - Esimo, Negesso; Hayicho, Hussien (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2024)
This study was aimed at characterizing and analyzing the morphometric parameters and their implications on the watershed in the sub-upper part of the Wabe Shebele drainage basin in the Melka Wakena sub-basin. To achieve the objective of the study, descriptive and empirical research methods were employed using different data types, such as DEM (30 mx 30 m), Ethio GIS 2007, and GCPs. The collected data were processed and analyzed using ArcGIS 10.3 tools and formulas coined by different scholars into basins with linear, areal, drainage, and relief aspects. Data analysis was carried out in a range of stages to determine the morphometric parameters of the study drainage basin. The study area covers 4372 km2. The finding indicates that the basin has a fourth-order drainage basin, with lower and middle-order streams dominating. The study discovered that large portions of the basin's topography are suitable for agriculture, with 54.33% being highly suitable, 42.97% being moderately suitable, and only 2.7% being unsuitable. The findings from the upper Wabe Shebele River Basin could provide useful empirical data for developing a strong physical soil and water resource conservation structure and management plan for long-term watershed management.